2022
DOI: 10.31579/2637-8892/159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Body Dysmorphic Disorder among Female Patients Seeking Cosmetic Procedures

Abstract: Background: Body dysmorphic disorder (BDD) is a psychiatric illness in which one’s with minimal or non-existing defect in appearance shows significant distress and impairment in behavior and psychosocial functioning. Patients with body dysmorphic disorder seeking cosmetic surgery are usually unsatisfied with the outcomes of the surgery; this is why it is an important subject to be focused on. Moreover, physicians should consider the assessment of body dysmorphic disorder before undergoing any cosmetic procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Studies have demonstrated that reducing rumination can lead to significant decreases in depressive symptoms and improvements in cognitive and emotional regulation (11,12). Furthermore, considering the high prevalence of BDD in clinical populations seeking cosmetic procedures and the significant distress and impairment associated with the disorder, there is a critical need for validated, effective treatments that address both the psychopathological features and the overall quality of life (15). This is particularly pertinent as BDD often goes unrecognized and untreated, contributing to severe psychological distress and a high burden of comorbidity with other mental disorders (16).…”
Section: Introduction Ody Dysmorphic Disorder (Bdd) Is Characterized Bymentioning
confidence: 99%
“…Studies have demonstrated that reducing rumination can lead to significant decreases in depressive symptoms and improvements in cognitive and emotional regulation (11,12). Furthermore, considering the high prevalence of BDD in clinical populations seeking cosmetic procedures and the significant distress and impairment associated with the disorder, there is a critical need for validated, effective treatments that address both the psychopathological features and the overall quality of life (15). This is particularly pertinent as BDD often goes unrecognized and untreated, contributing to severe psychological distress and a high burden of comorbidity with other mental disorders (16).…”
Section: Introduction Ody Dysmorphic Disorder (Bdd) Is Characterized Bymentioning
confidence: 99%